The great Greene heist - Johnson, Varian (Scholastic Inc., 2015)
Jackson Greene has a reputation as a prankster at Maplewood Middle School, but after the last disaster he is trying to go straight--but when it looks like Keith Sinclair may steal the election for school president from Jackson's former best friend, Gabriela, he assembles a team of talented troublemakers to make sure Keith does not succeed.